2016
DOI: 10.3389/fpls.2016.01459
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Genotype and Environment on Small RNA Profiles in Grapevine Berry

Abstract: Understanding the molecular mechanisms involved in the interaction between the genetic composition and the environment is crucial for modern viticulture. We approached this issue by focusing on the small RNA transcriptome in grapevine berries of the two varieties Cabernet Sauvignon and Sangiovese, growing in adjacent vineyards in three different environments. Four different developmental stages were studied and a total of 48 libraries of small RNAs were produced and sequenced. Using a proximity-based pipeline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 117 publications
4
27
0
Order By: Relevance
“…DNA methylation analysis also revealed differences between the genotypes, suggesting that epigenetic regulation may partially explain the variation between the genotypes in terms of gene expression in different environments, as recently postulated in the Shiraz cultivar (Xie et al ., ). A recent study based on the biological material used herein has also suggested that small RNAs have a buffering effect on transcriptomic plasticity in the widely cultivated Cabernet Sauvignon cultivar (Paim Pinto et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…DNA methylation analysis also revealed differences between the genotypes, suggesting that epigenetic regulation may partially explain the variation between the genotypes in terms of gene expression in different environments, as recently postulated in the Shiraz cultivar (Xie et al ., ). A recent study based on the biological material used herein has also suggested that small RNAs have a buffering effect on transcriptomic plasticity in the widely cultivated Cabernet Sauvignon cultivar (Paim Pinto et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…It is anecdotally known that many grapevine varieties perform differently in distinct environments, with some varieties such as Cabernet Sauvignon and Chardonnay offering more consistency and others such as Sangiovese, Nebbiolo and Pinot Noir showing greater variation. Most grapevine G×E studies have focused on single traits using classical methods such as the analysis of quantitative trait loci (Adam‐Blondon et al ., ), but we have recently explored the use of ‘omics’ approaches to unravel the phenotypic plasticity of grapevine berries on a broader scale (Dal Santo et al ., , ; Anesi et al ., ; Paim Pinto et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The data related to all the novel miRNAs identified so far in grapevine were collected from 18 already published works ( Carra et al, 2009 ; Pantaleo et al, 2010 , 2016 ; Wang et al, 2011 , 2012 , 2014 ; Alabi et al, 2012 ; Singh et al, 2012 ; Han et al, 2014 , 2016 ; Belli Kullan et al, 2015 ; Sun et al, 2015 ; Paim Pinto et al, 2016 ; Bester et al, 2017a , b ; Pagliarani et al, 2017 ; Snyman et al, 2017 ; Zhao et al, 2017 ). Each novel miRNA was aligned using BLAST both against the known miRNAs deposited in miRBase ( Kozomara and Griffiths-Jones, 2014 ) and against all the novel miRNAs retrieved by the different studies above cited.…”
Section: Methodsmentioning
confidence: 99%
“…In the last few years, from the first report concerning the identification of novel miRNAs in grapevine ( Carra et al, 2009 ), several works have been published on this topic, and many conserved and putative novel miRNAs were identified. Different species from the Vitis genus were analyzed, the most studied being several cultivars of Vitis vinifera ( Carra et al, 2009 ; Pantaleo et al, 2010 , 2016 ; Alabi et al, 2012 ; Belli Kullan et al, 2015 ; Sun et al, 2015 ; Paim Pinto et al, 2016 ; Bester et al, 2017a , b ; Pagliarani et al, 2017 ; Snyman et al, 2017 ) and the “Summer Black” hybrid of V. vinifera × Vitis labrusca ( Wang et al, 2011 , 2014 ; Han et al, 2014 ; Zhao et al, 2017 ). In addition, some miRNAs derived from Vitis amurensis ( Wang et al, 2012 ) and from a powdery mildew-resistant accession of the wild Chinese Vitis pseudoreticulata Baihe-35-1 ( Han et al, 2016 ) were characterized as well.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study focused on the basis of grapevine genotype × environment (G × E) interactions showed that, for example, the cv. 'Cabernet Sauvignon' was less dependent on growth conditions and that its transcriptome remained more stable across vintages and locations, suggesting that the limited plasticity of this French cultivar may underpin its success in many different parts of the globe (Dal Santo et al, 2018;Paim Pinto et al, 2016).…”
Section: Grapevine Origin and Domesticationmentioning
confidence: 99%